Academic Stress in the Psychological Well-being of Higher Education Students - Carlos GALLEGUILLOS; Rubén HURTADO; Claudia TRIGO; José SILVA; Dapne LEON (Communications of International Proceedings, 2023)
The purpose of this research was to determine the influence of academic stress on psychological well-being in higher education students. Four hypotheses were generated that dictate whether the physical reaction (h2) psychological reaction (h3) coping and (h4) academic stressors have an influence on the psychological well-being of students. The hypothetical model was tested through a non-probabilistic convenience sample of 200 higher education students. The construct validity of the SISCO measurement instrument was verified, finding that the physical and psychological reactions present a high degree of correlation, promoting an adjustment of the questionnaire. Thus, the results partially confirm the hypotheses. This is that the physical and psychological reaction is significant and is negatively related to the psychological well-being of the students. On the other hand, coping is significant and is positively related to psychological well-being. Finally, it is suggested that these results be understood according to the limitations of the study.
Keywords: psychological well-being; academic stress; coping.